Multidisciplinary team for genetic disorders – Integration with clinicians and health-care professionals - Mounika Endrakanti; Neerja Gupta (Apollo Medicine)
Individuals with genetic disorders present with multisystem, complex, and special health care needs. Although limited treatment options are available for most genetic conditions, ensuring continued ongoing surveillance and rehabilitative care is quintessential for improving their quality of life. Delivering comprehensive health-care directed at periodic surveillance, timely diagnosis, and specialized management of these individuals warrants ongoing evaluation and management by specialists in multiple disciplines. Multidisciplinary team approach involving coordinated care among various specialties with a patient-centric outlook ensures efficient resource utilization and cost-effective management. The establishment of “one-stop” multidisciplinary specialized clinics providing comprehensive care is expected to improve the quality of patient care and reduce the overall burden on the family.